Assessment of pSOFA-L score in predicting the clinical outcome of critically ill children - Kumbar, Shrishail; ., Chandrashekhara (International Journal of Contemporary Pediatrics, 2020)
Background: Recently Pediatric Sequential Organ Failure Assessment (pSOFA) score was adapted and validated in critically ill children to predict the clinical outcome. This study was aimed to evaluate the lactate level association with the outcome and thereby formulating pSOFA-L score to predict the clinical outcome better in critically ill children. Methods: This hospital based prospective, observational, analytical study was conducted in the Department of Paediatrics, A. J Hospital, Mangalore, Karnataka. Requirement of oxygen, inotrope support and other parameters were studied and compared the score with clinical outcome. A total of 75 cases were studied. Results: In this study total of 51 children had high serum lactate levels (68%). Out of 28 expired children 23 children had higher serum lactate levels that accounts for about 82.14% which is statistically significant (p<0.001). ROC curve of pSOFA-L score in predicting the mortality yielded AUC: 0.92 and cut off value: 10.5 which is statistically significant (p<0.001). In the present study mortality rate was 26.09% in children whose pSOFA-L score was less than 9 and mortality rate of 38.89% and 50.00% in children whose pSOFA-L score was 9 to 11 and more than 11 respectively. Conclusions: In this study increase in pSOFA-L score is associated with high mortality and poor outcome. The findings of the present study validate and emphasize that, pSOFA-L score helps in accurate prediction of mortality of critically ill children.